Critical review: Grand challenges in assessing the adverse effects of contaminants of emerging concern on aquatic food webs - Nilsen, Elena (2019)
Much progress has been made in the past decades to understand the sources, transport, fate andbiological effects of contaminants of emerging concern (CECs) in aquatic ecosystems. Despitethese advancements, significant obstacles remain to comprehensively assess the environmentalrisks associated with the presence of CECs. Many of these obstacles center around theextrapolation of effects of single chemicals observed in the laboratory or effects observed inindividual organisms or species in the field to impacts of multiple stressors on aquatic food webs.In the current review, we identified five challenges that need to be addressed to advance studiesof CECs from singular exposure events to multi-species aquatic food web interactions: (i) moredetailed information on the complexity of mixtures of CECs in the aquatic environment; (ii)understanding sub-lethal effects of CECs on a wide range of aquatic organisms; (iii) ascertainingthe biological consequences of variable duration CEC exposures within and across generations inaquatic species; (iv) linkage of multiple stressors with CEC exposure in aquatic systems; and (v)documenting the trophic consequences of CEC exposure across aquatic food webs. We reviewthe current literature to demonstrate how these challenges can be addressed to fill knowledgegaps.